Earthquake-resistant design of open ground storey RC framed buildings - Davis, Robin; Menon, Devdas; Prasad, Meher (Journal of Structural Engineering, 2025)
Open ground storey (OGS) buildings are known to be vulnerable under seismic loading due to early formation of collapse mechanism in the ground storey RC columns. The estimation of design forces in such buildings has not been adequately addressed in existing design codes and the literature. In the present study, four different methods are proposed, ranging from rigorous nonlinear dynamic analysis (NDA) of the infilled frame to simplified equivalent static analysis of the bare frame. All the methods proposed are found to result in similar estimates of the design forces in the ground storey columns. The linear analysis (static/dynamic) methods proposed are particularly simple to apply in practice, and will result in designs that are rational and economical, compared to the existing code-based methods